Reflective Management: The Heartbeat for Successful School Practices - M'Lingera, Meeme Julius; Guantai, Kiende (IJRDO- Journal of Educational Research, 2020)
Just as a human body cannot function without an active human heart, so is an educational institution that cannot thrive in the 21st century without an effective reflective manager. Therefore, modern-day educational institutions require that managers do not just rely on the various types and sources of power that is at their disposal nor on their dictatorial, bureaucratic or democratic tendencies, but they require managers that clearly understand who they are, who they are with, where they have come from, where they are, why they are where they are, where they are going, and why they are going there. For this to be possible, the managers require to embrace an effective reflective management practice that does not only help them focus on themselves but that also helps them think critically about the impact of their actions to themselves, to others and to the school. The purpose of this paper is to outline the importance, determinants and characteristics of reflective leadership in school management. It also addresses the Principles-Levels-Stages (PLS) model of reflective management practices comprising of 12 principles, 3 levels and 3 stages that are critical in directing managers into systematic logical thinking focusing not only on themselves but also on their interactions with others and the school that they are serving, in order to steer them to a competitive advantage.